1996
DOI: 10.1063/1.116848
|View full text |Cite
|
Sign up to set email alerts
|

The origin of blue and ultraviolet emission from porous GaP

Abstract: A comparative study of ultraviolet emission with peak wavelengths around 350 nm from oxidized porous silicon and that from SiO2 powder Interdiffusion of lateral composition modulated (GaP)2/(InP)2 shortperiod superlattices with different encapsulants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Indeed, an emission peak in the UV spectral region ͑Ͼ3 eV͒ has ever been observed on porous GaP and has been attributed to the quantum confinement of charged carriers in nanocrystalline GaP. 5,6 Meijerink et al 7 have also observed UV emission in porous GaP but concluded that the emission is due to gallium oxide on the surface of the porous material.…”
Section: Photoluminescence Measurementmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, an emission peak in the UV spectral region ͑Ͼ3 eV͒ has ever been observed on porous GaP and has been attributed to the quantum confinement of charged carriers in nanocrystalline GaP. 5,6 Meijerink et al 7 have also observed UV emission in porous GaP but concluded that the emission is due to gallium oxide on the surface of the porous material.…”
Section: Photoluminescence Measurementmentioning
confidence: 96%
“…[2][3][4] Like silicon, compound semiconductors such as GaP and GaAs have been investigated in the form of porous structures and many different properties relative to those of bulk materials have been reported. For instance, UV and visible emissions have been observed in the porous layers of GaP, [5][6][7] GaAs, 8,9 and InP. [10][11][12] Stable field electron emitters have been fabricated using porous GaP and GaAs layers.…”
Section: Introductionmentioning
confidence: 99%
“…Porous GaP, produced by anodic etching, is the most strongly scattering material for visible light, reported to date; 21 there is evidence for the onset of Anderson light localization 22 in this material. At low temperature, bulk GaP shows a sharp luminescence emission centered at around 560 nm which is quenched at room temperature; 23 macroporous GaP shows similar luminescent properties. 23 Doping the bulk semiconductor isoelectronically with nitrogen gives efficient near band-band luminescence at room temperature.…”
mentioning
confidence: 97%
“…At low temperature, bulk GaP shows a sharp luminescence emission centered at around 560 nm which is quenched at room temperature; 23 macroporous GaP shows similar luminescent properties. 23 Doping the bulk semiconductor isoelectronically with nitrogen gives efficient near band-band luminescence at room temperature. 24 Similar results are expected for macroporous GaP.…”
mentioning
confidence: 97%
“…2). This spectral distribution is quite different from that measured in a conventional photoluminescence experiment at ambient temperature [16,20]. Electroluminescence with peroxydisulfate, in which holes are injected into the valence band of GaP at negative potential, is shown in Fig.…”
Section: Methodsmentioning
confidence: 53%